Virtual education and COVID-19 - Rodriguez Córdova, Edin Daniel (2021)
This article is the result of the impact of virtual education in the context of the pandemic; therefore, I propose an approach from the academic and psycho-emotional aspect of university students. The core objective is to explain the relationship between both aspects and for this I will consider factors such as stress, emotional condition, academic performance, dropout, classroom connectivity and e-learning enhancement. All of this with the aim of making known the reality that we university students are going through, as well as proposing solutions to the problems that arise in each of these factors.